HPLC with Post-Column Derivatization with Alizarin for Determination of OATD-02, an Anticancer Arginase Inhibitor in Clinical Development - Elzbieta Sobolewska; Magdalena Tyszkiewicz; Roman Blaszczyk; Magdalena Biesaga (Applied Sciences, 2023)
The aim of this study was to develop an analytical method for selective determination of OATD-02 by high-performance liquid chromatography (HPLC) with post-column derivatization and fluorescence detection (FLD). OATD-02, a new boronic acid derivative, is a highly potent anticancer arginase inhibitor in clinical development. Chromatographic analysis of OATD-02 poses problems because this molecule has weak ultraviolet absorption. The derivatization reaction was based on the reaction between boronic acid from OATD-02 and alizarin solution. The optimized mobile phase consisted of a mixture of sodium bicarbonate in water and acetonitrile at a flow rate of 0.50 mL/min. Alizarin solution in methanol was delivered at a flow rate of 0.50 mL/min. The fluorescent complexes were detected by a fluorescence detector (excitation and emission wavelengths at 470 and 580 nm, respectively). The present method demonstrated proper values for selectivity, linearity, recovery (>99%), precision (RSD: 0.6%), sensitivity (LOD: 20 µg/mL and LOQ: 50 µg/mL), stability of solutions, and robustness.